Pengaruh Corporate Social Responsibility (CSR), Likuiditas, dan Pertumbuhan Penjualan Terhadap Profitabilitas Perusahaan Pada Perusahaan Sektor Barang Baku Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2021 - Noviani Adilla; Zalida Afni; Eka Siskawati (Politeknik Negeri Padang, 2023)
This study aims to analyze the factors that affect corporate social responsibility, liquidity, and sales growth on profitability in raw goods sector companies listed on the IDX in 2018-2021. The theory used in this research is Stakeholder Theory within the variable of Corporate Social Responsibility (CSR), Liquidity, Sales Growth as independents variables, and the dependent variable was profitability proxied by ROA. The population of this research was goods sector companies listed on the IDX in 2018-2021. The sampling with a total of samples are 28 companies from 93 populations. This research method used a quantitative approach with the analysis technique used, panel data regression analysis. This study used secondary data in the form of annual report and sustainability report which id processed with the SPSS version 25. The results show that Corporate Social Responsibility (CSR) and sales Growth both negatively effects the profitability, but liquidity has no effects to words profitability.